A roadmap to recovery and a life worth living: An interpretative phenomenological analysis of adolescent experiences of dialectical behaviour therapy in child and adolescent mental health services - Ní Mhaoláin, Clodagh; MacNeela, Pádraig (European Journal for Qualitative Research in Psychotherapy, 2021)
This research explores adolescents’ lived experience of 24 weeks of Dialectical Behaviour Therapy (DBT), designed to address severe mental health difficulties including suicidal and self-harming behaviour. There is a lack of published literature regarding adolescent lived experiences of 6 months comprehensive DBT. A qualitative design in the form of Interpretative Phenomenological Analysis (IPA) is an appropriate fit for research questions concerned with individual phenomenology. Six adolescent service users self-selected to take part in the research. One superordinate theme around recovery of mental health and wellbeing was characterised as ‘building a roadmap to recovery and a life worth living’. Three subordinate themes depict the steps on the road and describe how individuals travelled from ‘alienation to insight’, ‘isolation to connection’, and from ‘passive disempowered recipient of intervention to proactive engagement as empowered service users’. Novel links between DBT, identity process theory, attachment theory and critical psychology are made.